Sarı Abdullah Efendi ve Mesnevi-i şerif şerhi - Aytekin, Ülker (My University, 2002)
TEZ ÖZETİ Çalışmamız Sarı Abdullah efendi'nin Mesnevî şerhini konu almıştır. Mevlânâ'nın vefâtından 400 sene sonra yazılan bu şerh, diğer Mesnevî şerhleri arasında en geniş açıklamaları sunan tek şerhtir. Çalışmamız bir giriş ve üç bölümden oluşmaktadır. Giriş bölümünde Abdullah Efendi'nin yaşamış olduğu devrin yâni m. XV: yüzyılın siyâsî , ekonomik ve sosyal durumu ve ayrıca Abdullah Efendi'nin mensup olduğu Melâmî tarîkatının durumu özetlenmiştir. Birinci bölümde şârihin hayatı, şeyhleri, eserleri, müridleri üzerinde durulmuştur. Bu bölümde en önemli bilgi şârihin ilk telif ettiği eser olan Semerâtü'l-Füâd'ın melâmîlerin iki anlayışının temelleri atmış olmasıdır. Bu eserin yazım amacı bütün tarîkatların tek silsilede toplamış olmasıdır. Bu özellik sâyesinde Melâmîler diğer tarîkatlara girmişler ve bu tarîkatlarda faaliyet göstermişlerdir. Ancak zaman içinde başka tarîkatlar içinde erimiş ve melâmî neşesi tâbiri ortaya çıkmıştır. İkinci bölümde şerhin özellikleri üzerinde durulmuştur. Özellikle devrin melâmî târihe ışık tutması ve kullandıkları bâzı tâbirleri açıklayan pasajlar değerlendirilmiştir. Şerhin kaynaklarının eserin içinde zikredilmiş olması dikkat çekicidir. Bu eserlerin sayıca yüzün üzerindedir; alan olarak hemen hemen tüm İslâmî ilimleri kapsayacak niteliktedir. Şerh, bu yönüyle hem Mesnevî'nin anlaşılması için gerekli birikimi hem de Abdullah Efendi'nin ilmî vüsatini göz önüne sermektedir. Üçüncü bölüm ise başta Mesnevî'nin ilk on sekiz beyti olmak üzere , ilk ciltteki hikâyelerde kullanılan sembollerin çözümü üzerinde durulmuştur. Abdullah Efendi'nin sembollere âit şerhi ile özellikle muâsırı Ankaravî'nin şerhi mukâyese yapılmıştır.

The study aims to examine the Sar?ı Abd allah Efendi's (992-1071 / 1584-1661) Mathnawi commentary the Cevâhir-i Bevâhir-i Mesnevî. The Mathnawi is -the greatest mystical poets of all times- Maulana Jalal al-Din Rumi's (1207-1273) poem book. With need of understanding the poem and symbols in the Mathnawi , many numbers of commentaries have been written. Our thesis is on the commentary of Sarı Abd alllah Efendi, the member of Bayrâmî-Melâmî order. He wrote his commentary four certuries later from Maulana. The goals of the work are to clarify the characteristics and the importance of Abd allah Efendi's Turkish Mathnawi commentary, comparing with the others Turkish commentaries especially with his comtemporary Ankaravî's. The study contents a preface and three chapters: In the preface we researched political, economic coditions and situation Islamic sciences and scolars and especially Melâmi order whose two ?şeyhs were executed. XVI. century was very hard time for Melâmîs. So they had to use two concepts to save themselves: Ketm-i meslek [ to hide of the order] and terkîb-i hafâ [ to compose -of orders to- hide ] The firs chapter is on Abd allah Efendi's life story, his studies, his mürids. The most important point in this chapter is his book Semerâtü'l-Fuâd which describes the terkîb-i hafâ: All of the order's lines (silsile) unites under the same point: The Prophet and Ali. By these concept many numbers of Melâmî members like Abd allah Efendi joined the other orders especially which got both Alevî and Si?ddîkî line for example Nak?shibendiyye, Mevleviyye, Halvetiyye,Bayramiyye... By practice of terkîb-i hafâ Melâmî members were saved from attacks. By the time, Melâmî line was fused in the other orders. And melâmet became a manner in the other orders. The second chapter is on the characteristics and importance of the commentary. What is the title, when is wrote, where is published etc. This commentary is for only the first volume of the Mathnawi. It is not a simple commentary, it's an encyclopedic dictionar?y about of mysticism. It cointains main terms like fakr, vecd , vuslat, tahakkuk etc. There are lots of Quranic verses and Hadith commentary with very long passages. So we can say that this commentary is a Quranic commentary, too. The main characsteristic of the commentary is to present knowledge for Melâmî order which is hidden from people. Many terms used by members of this order, are explained. So we can say that this commentary is a very important discourse for the Melâmi order. He used a large number discourses on history, tefsir, hadith, phylopsophy, other Mathnawi commentaries, literature... . These discourses are over 100 books . Cevâhir-i Bevâhir-i Mesnevî exemplifies that to understand to the Mathnawi , whow large-scale knowledge we have to have. This commentary also shows Abd allah Efendi's scientific largeness on all Islami?c scienses and his expertise on the Mathnawi. Because of his expertise on the Mathnawi he was named The Commentier of the Mathnawi The third chapter is on the Mathnawi symbols . We researched the his commentaries on the Mathnawi compairing with Ankaravi's commentary story by story and symbol by symbol. We clarified different point of views of explanations to symbols.
Keywords: Akâid ve Kelâm; Din; İslam Dini; Mesnevi; Tasavvuf Islamiyet